2012
DOI: 10.1007/s11434-012-5095-1
|View full text |Cite
|
Sign up to set email alerts
|

Quantum information and many body physics with cold atoms

Abstract: We review our recent theoretical advances in quantum information and many body physics with cold atoms in various external potential, such as harmonic potential, kagome optical lattice, triangular optical lattice, and honeycomb lattice. The many body physics of cold atom in harmonic potential is investigated in the frame of mean-field Gross-Pitaevskii equation. Then the quantum phase transition and strongly correlated effect of cold atoms in triangular optical lattice, and the interacting Dirac fermions on hon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…cross-coupling products were obtained in 21-67% yields, using 0.2-0.5 mol% of this iron catalyst in tetrahydrofuran at 25 °C for 12 hours. 37 In 2012, Knochel reported a simple and practical ironcatalyzed cross-coupling of N-heterocyclic chlorides and bromides with arylmagnesium reagents. 38 The addition of an ethereal cosolvent, such as diethyl ether or tert-butyl methyl ether, was essential to prevent homocoupling side reactions and led to high yields.…”
Section: Short Review Syn Thesismentioning
confidence: 99%
“…cross-coupling products were obtained in 21-67% yields, using 0.2-0.5 mol% of this iron catalyst in tetrahydrofuran at 25 °C for 12 hours. 37 In 2012, Knochel reported a simple and practical ironcatalyzed cross-coupling of N-heterocyclic chlorides and bromides with arylmagnesium reagents. 38 The addition of an ethereal cosolvent, such as diethyl ether or tert-butyl methyl ether, was essential to prevent homocoupling side reactions and led to high yields.…”
Section: Short Review Syn Thesismentioning
confidence: 99%
“…By tuning the interaction strength, the system switches between two distinct phases corresponding to the two possible ground states: the delocalized superfluid (SF) and the localized Mott-insulating (MI) state [12][13][14][15][16][17]. The relatively recent innovation of synthetic materials, made possible with ultracold atomic gases, has added a vitally important tool to study many-body physics in experimental systems [6,[18][19][20][21][22][23][24]. Such systems have been used to study the SF-MI transition [25,26] including finite-temperature properties [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26] The first examples with anionic aryloxo-functionalized NHCs, were reported by Shen et al 27,28 Lavoie and co-workers reported the complexes with neutral imine-functionalized NHCs. 29,30 The group of Hahn and Chen reported the octahedral complexes with pyridinyl 31 and pyrimidinyl 32,33 substituted NHC respectively. Herein, we report the syntheses and structures of a series of iron complexes of a bidentate picolyl-NHC ligand, along with their reactivity including the interconversions, transmetalation, C-C bond formations, and ligand deprotonation accompanied by the dearomatization of the pyridine moiety.…”
Section: Introductionmentioning
confidence: 99%